THE TENDENCY OF DRAMATISM IN JAMAL KAMAL'S POETRY (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The article discusses the dramatic scenes in Jamal Kamal's poetry as a result of polyphonic imagery, their unique poetic features, genesis, artistic appeal, richness of intellectual generalizations, social appeal and repercussions.